Pengaruh Likuiditas, Solvabilitas, Profitabilitas dan Nilai Pasar Terhadap Harga Saham Sektor Industri Dasar dan Kimia Di Bursa Efek Indonesia Periode 2013-2016 - Muhammad Mukhsin; Ninik Lukiana; Hartono Hartono (Ecobuss, 2018)
The purpose of this research is to find the influence of liquidity, solvability, profitability, and market value of stock prices the industrial sector base and chemical in Indonesia stock exchange 2013-2016 period, whether partial and simultaneously, and to know variables influential dominant to share prices. The methodology used is statistics method linear regression multiple. The sources and types of the data used were internal data and secondary in the form of the annual financial report. The sample techniques used in research is sampling purposive, and produce 20 firms as the sample. The research results show simultaneously variable liquidity and the solvability has no significant impact on the price of the stock, variable while reducing the market value of significant impact on the price of the stock with a variable that exerts influence dominant is the market value of. Simultaneously liquidity , the solvability , its satisfactory profitability as, and the market value of significant impact on the price of the stock coefficient of determination (r square) obtained value of 0,400 which indicates that 40% stock prices can be explained by liquidity, the solvability, its satisfactory profitability as, and the market value of the remaining 60% stock prices influenced by other variables subjects in this study. The limited number of this research is only examines the influence of liquidity, the solvability, its satisfactory profitability as, and the market value of a stock on the prices. While the other variables that affect the price of the stock is expected to researched by next researchers. Keyword: Liquidity, Solvability, Profitability, Market Value, Stock Prices.